HIV-positive status and preservation of privacy: a recent decision from the Italian Data Protection Authority on the procedure of gathering personal patient data in the dental office. Issue 6 (7th February 2012) - Conti, Adelaide; Delbon, Paola; Laffranchi, Laura; Paganelli, Corrado; De Ferrari, Francesco
Abstract : The processing of sensitive information in the health field is subject to rigorous standards that guarantee the protection of information confidentiality. Recently, the Italian Data Protection Authority (Garante per la Protezione dei Dati Personali) stated their formal opinion on a standard procedure in dental offices involving the submission of a questionnaire that includes the patient's health status. HIV infection status is included on the form. The Authority has stated that all health data collection must be in accordance with the current Italian normative framework for personal data protection and respect the patient's freedom. This freedom allows the patient to decide, in a conscious and responsible way, whether to share health information with health personnel without experiencing any prejudice in the provision of healthcare requested. Moreover, data collection must be relevant and cannot exceed the principles of treatment goals with reference to the specific care of the concerned person. However, the need for recording information regarding HIV infection at the first appointment, regardless of the clinical intervention or therapeutic plan that needs to be conducted, should not alter the standard protection measures of the healthcare staff. In fact, these measures are adopted for every patient.